Determinants and Strategies for Improving Adolescent Reproductive Health in Indonesia - Roichatul Djannah (International Journal of Multidisciplinary Research and Literature, 2024)
Adolescent reproductive health is a public health issue requiring promotive, preventive, and youth-friendly service approaches. National studies indicate that knowledge, attitudes, media exposure, school support, parental roles, and the availability of adolescent-friendly health services such as PKPR and youth information and counseling centers such as PIK-Remaja influence adolescent reproductive health behavior. This article aimed to synthesize determinants and improvement strategies for adolescent reproductive health based on five Indonesian articles published between 2019 and 2023. A systematic literature review with narrative synthesis was applied. The reviewed articles included cross-sectional quantitative studies, a qualitative study, and community service articles addressing adolescent sexual behavior, sexual media exposure, PKPR utilization, PIK-Remaja, reproductive health education, peer cadres, and parental involvement. The synthesis identified four major themes: (1) knowledge alone is insufficient to prevent risky sexual behavior without attitude formation, social control, and media literacy; (2) PKPR services should be youth-friendly, confidential, and culturally sensitive; (3) PIK-Remaja, peer cadres, and reproductive-health-oriented schools are effective educational and mentoring channels; and (4) promotion, reproductive health education, and parental roles contribute to better adolescent service utilization. In conclusion, adolescent reproductive health improvement requires an integrated model based on schools, families, youth-friendly health services, digital media literacy, and peer counselor strengthening